Enhancing Women's Resilience in Disaster Condition in Padang City West Sumatra Province - Rahayu, Wewen Kusumi; Purwanti, Anik; Astuti, Retno Sunu; Lituhayu, Dyah (Ridwan Institute, 2023)
Padang City is one of West Sumatra Province's Level II Regions. Padang is geographically vulnerable to natural disasters, particularly earthquakes and tsunamis. Natural disasters affect men and women differently. Women are four times more likely than men to become victims of natural disasters. Women, on the other hand, have become advocates for the existence of various government disaster relief efforts. The Regional Government of Padang City actively maximized the position of women as one of the agents who became a support and fixed the post-natural disaster situation, according to a descriptive qualitative method and the theory of social feminism. The purpose of this study is to determine the position of women actively as one of the agents who support and improve the situation after natural disasters. Using a descriptive qualitative method with the theory of social feminism, it was found that the Padang City Regional Government has maximized the position of women actively as one of the agents who support and improve the situation after natural disasters. The efforts of the local government are aided by West Sumatra's adoption of local matrilineal values, which place women as the primary party in the concept of kinship life. Women's resilience in disaster mitigation conditions can be increased by actively involving them.